Changes in weight loss‐related quality of life among type 2 diabetes mellitus patients treated with dapagliflozin. Issue 7 (9th February 2014) - Grandy, S.; Hashemi, M.; Langkilde, A.‐M.; Parikh, S.; Sjöström, C. D.
<x xml:space="preserve">Abstract</x> Aims This study evaluated change in health‐related quality of life (HRQOL) associated with ongoing weight change among patients with type 2 diabetes mellitus (T2DM) treated with dapagliflozin, a highly selective sodium‐glucose cotransporter 2 (SGLT2) inhibitor that lowers blood glucose by increasing urinary glucose excretion and is associated with body weight reductions. Methods Patients with T2DM who had inadequate glycaemic control on metformin (MET) alone were enrolled in a 24‐week, double‐blind, randomized, placebo‐controlled study with a 78‐week extension to evaluate the effect of dapagliflozin + MET on body weight. Patients also completed the Study to Help Improve Early evaluation and management of risk factors Leading to Diabetes Weight Questionnaire‐9 (SHIELD‐WQ‐9), a weight change‐related HRQOL survey. Difference in proportions of patients treated with dapagliflozin 10 mg + MET (n = 89) or placebo + MET (n = 91) who reported improvement in HRQOL was analysed with Fisher's exact test. Results Dapagliflozin patients had significantly greater weight loss than placebo patients over 102 weeks (p < 0.05). This corresponded to a numerically greater proportion of dapagliflozin‐treated patients reporting ongoing weight loss and associated improvements in most HRQOL domains at three different evaluation points (weeks 24, 50 and 102) than placebo‐treated patients. In a post‐hoc analysis among patients who reported ongoing weight loss regardless of treatment arm, a significantly greater proportion of patients reporting weight loss versus weight gain reported improvements in physical health, self‐esteem and overall HRQOL at weeks 24, 50 and 102. Conclusions Dapagliflozin‐induced weight loss was associated with improvement in overall HRQOL. Overall, ongoing weight loss was associated with improvements in several HRQOL domains compared with weight gain.